Abuso sexual y sus consecuencias psicológicas en niñas y niñas de 4 a 12 años de edad, en el centro de protección casita de mis sueños de la Ciudad de Machala, en el año 2013. - Feijoo Encalada, Maily Evelyn (2013)
The development and application of this research work is based exclusively on knowing the psychological consequences of sexual abuse in children 4 to 12 years of age, in the protection center Casita de Mis Suenos city of Machala, which cause a concern of those working in this institution by increasing cases of child victims of sexual abuse.